Water extractable plant nutrients in soils amended with cow manure co-composted with maple tree residues - Anwar, Zobia; Irshad, Muhammad; Ping, An; Hafeez, Farhan; Yang, Shao (International Journal of Agricultural and Biological Engineering, 2018)
Studies on the availability of plant nutrients in soils treated with manure co-composted feed-stocks are very rare. The present investigation aimed at studying the nutrient release pattern from three soils amended with maple tree leaves co-composted with cow manure. Soils were mixed with the compost at the rate of 20 t/hm2 and incubated at room temperature. Prior to incubation, plants residue samples were analyzed for total elemental concentrations (NO3, NH4, P, K, Ca, Mg, Na, Zn, Mn, Fe, Cu, Ni and Cd). Water extractability of nutrients from soils was affected by the type of soil and ratio of composted manure applied. Extractable NH4, P, K, Ca and Mg concentrations varied in the descending order of sandy clay, sandy loam and silt loam except NO3. The concentrations of P, K, Ca and Mg in the amended soils increased with the ratio of manure co-composted with leaf litter while those of NO3, NH4 and trace elements decreased. The residual nutrients in soil varied directly with their contents in the compost amendments. Co-composting improved the availability of nutrients in soils and this should be an ideal approach to managing the enormous waste generated from the livestock sector for restoring soil fertility. Keywords: macro-elements, micro-elements, varied textured soils, co-composting, cow manure, maple plant residues DOI: 10.25165/j.ijabe.20181105.3494 Citation: Anwar Z, Irshad M, Ping A, Hafeez F, Yang S. Water extractable plant nutrients in soils amended with cow manure co-composted with maple tree residues. Int J Agric & Biol Eng, 2018; 11(5): 167–173.